Inflammation and activity augment brain-derived neurotrophic factor peripheral release. (24th March 2016) - Qiao, L.Y.; Shen, S.; Liu, M.; Xia, C.; Kay, J.C.; Zhang, Q.L.
Highlights: Depolarization evoked BDNF release to nerve terminals. BDNF released to the visceral organ in vivo . Both BDNF and pro-BDNF content were increased in the viscera in response to inflammation. TrkB and p75 expression/activity were increased during inflammation. Abstract: Brain-derived neurotrophic factor (BDNF) release to nerve terminals in the central nervous system is crucial in synaptic transmission and neuronal plasticity. However, BDNF release peripherally from primary afferent neurons has not been investigated. In the present study, we show that BDNF is synthesized by primary afferent neurons located in the dorsal root ganglia (DRG) in rat, and releases to spinal nerve terminals in response to depolarization or visceral inflammation. In two-compartmented culture that separates DRG neuronal cell bodies and spinal nerve terminals, application of 50 mM K + to either the nerve terminal or the cell body evokes BDNF release to the terminal compartment. Inflammatory stimulation of the visceral organ (e.g. the urinary bladder) also facilitates an increase in spontaneous BDNF release from the primary afferent neurons to the axonal terminals. In the inflamed viscera, we show that BDNF immunoreactivity is increased in nerve fibers that are immuno-positive to the neuronal marker PGP9.5. Both BDNF and pro-BDNF levels are increased, however, pro-BDNF immunoreactivity is not expressed in PGP9.5-positive nerve-fiber-like structures. Determination of receptor profiles in the inflamed bladder demonstrates that BDNF high affinity receptor TrkB and general receptor p75 expression levels are elevated, with an increased level of TrkB tyrosine phosphorylation/activity. These results suggest a possibility of pro-proliferative effect in the inflamed bladder. Consistently we show that the proliferation marker Ki67 expression levels are enhanced in the inflamed organ. Our results imply that in vivo BDNF release to the peripheral organ is an important event in neurogenic inflammatory state.